1998
DOI: 10.1046/j.1365-3148.1998.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Clostridium perfringens sepsis from a pooled platelet transfusion

Abstract: A male patient with acute myeloid leukaemia received a pooled platelet preparation prepared by Optipress system on the last day of its shelf life. The patient collapsed after two-thirds of the contents had been transfused. Clostridium perfringens was isolated from the platelet bag within 18 h of the acute event. Metronidazole, gentamicin and Clostridium antiserum were then administered in addition to the broad spectrum antibiotics started previously. However, the patient died 4 days after the platelets were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
2
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 9 publications
5
84
2
4
Order By: Relevance
“…are picked up later, and there are extra costs involved. However, anaerobic bacteria have been reported in fatal septic transfusion incidents (McDonald et al, 1998). Altogether, culture methods are still the method of choice but incapable of providing complete safety and other, especially faster, methods are sought.…”
Section: Slow Implementation Of the Pyrogen Test For Medical Devicesmentioning
confidence: 99%
“…are picked up later, and there are extra costs involved. However, anaerobic bacteria have been reported in fatal septic transfusion incidents (McDonald et al, 1998). Altogether, culture methods are still the method of choice but incapable of providing complete safety and other, especially faster, methods are sought.…”
Section: Slow Implementation Of the Pyrogen Test For Medical Devicesmentioning
confidence: 99%
“…are picked up later, and there is extra cost involved. However, anaerobic bacteria have been reported in fatal septic transfusion incidents (McDonald et al, 1998). Altogether, culture methods are incapable of providing complete safety, and other, especially quicker methods, are sought.…”
Section: Cellular Therapeuticsmentioning
confidence: 99%
“…1 Nucleic acid detection methods for HIV and hepatitis C (HCV) have reduced the window period for infectious risk, but may not eliminate transfusion-associated HIV 2 or HCV infections; 3 fatal bacterial infections caused by transfusion of platelet concentrates continue to be reported. 4 To improve the safety of platelet and plasma transfusion, a nucleic acid-targeted photochemical treatment (PCT) using the psoralen compound amotosalen HCl (S-59) and longwavelength ultraviolet A (UVA) light was developed to inactivate viruses, bacteria, and protozoa that may contaminate platelet and plasma components. 5,6 Preclinical studies have demonstrated inactivation of more than 10 6 infectious HIV particles, more than 10 5 infectious hepatitis B (HBV) and HCV particles, and a broad spectrum of gram-positive and gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%